Penegasan Peran Agama Dalam Kehidupan Berbangsa Di Indonesia : Reaffirming the Role of Religion in National Life in Indonesia - naufal arisyah; Mutiara Fahmi; Delfi Suganda (Journal of Indonesian Comparative of Syari'ah Law, 2026)
The administration of government in a modern rule-of-law state often encounters challenges when public policies are considered legally valid in a formal sense but raise concerns regarding substantive justice, public welfare, proportionality of authority, protection of fundamental rights, and leadership accountability. This condition indicates the need for an analytical framework that goes beyond formal legal compliance and incorporates foundational values underlying state governance. This study aims to examine the relevance of the principles of siyāsah shar‘iyyah namely justice, public interest (maslaḥah), balance, protection of religion and life, and leadership trustworthiness within Indonesia’s legal system and governmental policies. This research employs a normative legal method using statutory and conceptual approaches by analyzing the Constitution, statutory regulations, and relevant government policies. The findings demonstrate that the principles of siyāsah shar‘iyyah have substantial relevance to Indonesia’s national legal framework, particularly the 1945 Constitution of the Republic of Indonesia and various sectoral regulations. These principles are reflected in guarantees of equality before the law, orientation toward public welfare, proportional limitations on state authority, protection of the right to life and freedom of religion, and the strengthening of governmental accountability. Therefore, siyāsah shar‘iyyah can serve as an analytical instrument for evaluating and formulating public policies that are just and accountable.